Cost-effectiveness of 2-dose human papillomavirus vaccination for 12-year-old girls in Zhejiang Province: implications for China's expanded program on immunization. Issue 7 (2nd July 2020) - Luo, Yan; He, Hanqing; Tang, Xuewen; Wang, Shenyu; Zhang, Jun; Wu, Ting; Chen, Zhiping
ABSTRACT: Background: The high cost and insufficient supply of HPV vaccines have substantially slowed their implementation in lower-income countries. This study aimed to assess the incremental cost-effectiveness of two doses of human papillomavirus (HPV) vaccination (bivalent 16/18 vaccine; 2vHPV) compared to a no-vaccination scenario and a three-dose scenario in one province in China. Methods: A static Markov model was used to model a lifetime cohort of 100, 000 girls aged 12 years at the start of vaccination. A two-dose vaccination schedule was assumed to be non-inferior to a three-dose schedule in terms of vaccine efficacy, and both vaccination schemes were assumed to provide lifelong protection. Incremental costs, health effects and incremental cost-effectiveness ratios were used to measure the outcomes when comparing the different strategies. Results: Compared to no vaccination, the incremental cost-effectiveness ratio (Chinese yuan per quality-adjusted life year) of the two-dose vaccination strategy is 12, 472, and the 2-dose strategy is calculated to be cost saving relative to the 3-dose vaccination strategy. Conclusions: Introducing the 2vHPV vaccine would be highly cost effective at a per-dose vaccine price of CNY 500, which has implications for cervical cancer control in China and other resource-limited countries.